RENAL DAMAGE WITH MALIGNANT NEOPLASMS - I. B. Kolina; I. N. Bobkova (Klinicist)
The relationship between renal damage and malignant neoplasms is one of the most actual problems of the medicine of internal diseases. Very often, exactly availability of renal damage determines the forecast of cancer patients. The range of renal pathologies associated with tumors is unusually wide: from the mechanical effect of the tumor or metastases on the kidneys and/or the urinary tract and paraneoplastic manifestations in the form of nephritis or amyloidosis to nephropathies induced with drugs or tumor lysis, etc. Thrombotic complications that develop as a result of exposure to tumor effects, side effects of certain drugs or irradiation also play an important role in the development of the kidney damage. The most frequent variants of renal damage observed in the practice of medical internists (therapists, urologists, surgeons, etc.), as well as methods of diagnosis and treatment approaches are described in the article. Timely and successful prevention and treatment of tumor-associated nephropathies give hope for retaining renal functions, therefore, a higher life standard after completion of anti-tumor therapy. Even a shortterm episode of acute renal damage suffered by a cancer patient must be accompanied with relevant examination and treatment. In the caseof transformation of acute renal damage into the chronic kidney disease, such patients need systematic and weighted renoprotective therapy and correct dosing of nephrotoxic drugs.